If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3((6x-3)/3)-3(9x+9)=0
We multiply parentheses
3((6x-3)/3)-27x-27=0
We multiply all the terms by the denominator
3((6x-3)-27x*3)-27*3)=0
We add all the numbers together, and all the variables
3((6x-3)-27x*3)=0
| 0=(−2k3−7k2+5k)+(6k2+3k) | | 9*x=990 | | -5c+6+8=-16 | | 11=10b-19 | | 6.4(2k3)=19.2 | | 8(x-4)2x=-10 | | X*5x=6x | | 17m^2-33m=0 | | 10v^2-17v=0 | | -34(x)−1.72=−6.82 | | -2k=15 | | v^2-33v=0 | | 12k^2+49k=0 | | h+3.2=-3.2 | | 6x=42+x | | 40g^2-11g=0 | | 72+4w=12w | | (120-x/100)=100 | | -18.2=-2.6v | | 120-x/100=100 | | 3(2x-4)+10=4x+10 | | 15-w=4w | | 4x/3=87 | | 24+3x=3x+2(7-1) | | 13f^2+30f=0 | | 2x=156=4x+192 | | 219-y=130 | | 40x^2-134x+3.33=0 | | 2x+156=4x=152 | | 143-y=276 | | 13.6=1.7z+51 | | 9x-3=3(3x-2) |